Analysis of European Central Bank policies in times of European debt crisis - Savkanič, Tomáš; Havlíček, David, 1985-; Janda, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
The U.S. financial crisis has compelled financial meltdowns on diverse global financial markets. Unsettled position of European banks, credit crunch and market freeze severely affected European market and consequently led to European sovereign-debt crisis in 2009. Some European countries became incapable of paying off their government debts which forced European Central Bank to step in as a major party to resolve Eurozone crisis. Main policies consisted of unlimited bond purchases, cheap loans to banks, cutting banks' reserve requirements and lowering of interest rates. The thesis will explain the redefinition of European Central Bank role on post-2012 European Market to maintain strengthening of the European robustness and augmenting the Eurozone competitiveness on international markets. The thesis aim is to analyze the effectiveness of European Central Bank policies by determining their total costs and overall impact on the Euro area gross domestic product, inflation and unemployment rate. The thesis will strive to explain why American bailout costs had more positive impact on U.S. economy compared to the situation in Euro area. In the end, the thesis will summarize the efficaciousness of ECB programs in the long run and conclude the advantages and disadvantages of both the European and the American approach in resolving the global financial crisis.
Vedoucí práce: David Havlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses